Decrease in exhaled hydrogen as marker of congestive heart failure. Issue 2 (12th September 2018) - Shibata, Atsushi; Sugano, Yasuo; Shimouchi, Akito; Yokokawa, Tetsuro; Jinno, Naoya; Kanzaki, Hideaki; Ohta-Ogo, Keiko; Ikeda, Yoshihiko; Okada, Hideshi; Aiba, Takeshi; Kusano, Kengo; Shirai, Mikiyasu; et al.
Abstract : Objective : Hydrogen excretion is thought to be related to systemic antioxidation activity. H2 selectively reduces the hydroxyl radical of free hydrogen (·OH), a highly cytotoxic form of reactive oxygen species, in cultured cells. Methods: We investigated whether exhaled H2 decreased during night sleep, reflected ·OH production and was associated with heart failure severity. We enrolled 108 patients with chronic heart failure (CHF) and 15 control participants without CHF. H2 concentration was measured by gas chromatography in exhaled breath collected before sleep and in the morning after overnight fasting. Overnight change in H2 concentration (ΔH2 ) was calculated. Mitochondrial morphology evaluated by transmission electron microscopy in endomyocardial biopsies collected from 18 patients with dilated cardiomyopathy. Results: ΔH2 was significantly lower in patients with CHF compared with controls (−4.3±1.0 vs 2.0±2.1 ppm, p=0.030) and was positively correlated with cardiac index (CI; r = −0.285, p=0.003). Patients with a ΔH2 <0 ppm had a significantly lower CI compared with those who had a ΔH2 >0 ppm (2.85±0.61 vs 3.24±0.65 L/min/m 2, p=0.005). ΔH2 was negatively correlated with both the percentage of vacuole-containing mitochondria and indices of cristae remodelling (r = −0.61, p=0.007). Conclusions: Decrease in exhaled H2 during night sleep was associated with CHF severity. ΔH2 warrants investigation as marker of CHF severity.